Neutrophil extracellular traps mediate transfer of cytoplasmic neutrophil antigens to myeloid dendritic cells toward ANCA induction and associated autoimmunity - Sangaletti, Sabina; Tripodo, Claudio; Chiodoni, Claudia; Guarnotta, Carla; Cappetti, Barbara; Casalini, Patrizia; Piconese, Silvia; Parenza, Mariella; Guiducci, Cristiana; Vitali, Caterina; Colombo, Mario P. (Blood, 2012)
Antineutrophil cytoplasmic antibodies (ANCAs) target proteins normally retained within neutrophils, indicating that cell death is involved in the autoimmunity process. Still, ANCA pathogenesis remains obscure. ANCAs activate neutrophils inducing their respiratory burst and a peculiar form of cell death, named NETosis, characterized by formation of neutrophil extracellular traps (NETs), decondensed chromatin threads decorated with cytoplasmic proteins endorsed with antimicrobial activity. NETs have been consistently detected in ANCA-associated small-vessel vasculitis, and this association prompted us to test whether the peculiar structure of NET favors neutrophil proteins uploading into myeloid dendritic cells and the induction of ANCAs and associated autoimmunity. Here we show that myeloid DCs uploaded with and activated by NET components induce ANCA and autoimmunity when injected into naive mice. DC uploading and autoimmunity induction are prevented by NET treatment with DNAse, indicating that NET structural integrity is needed to maintain the antigenicity of cytoplasmic proteins. We found NET intermingling with myeloid dendritic cells also positive for neutrophil myeloperoxidase in myeloperoxidase-ANCA-associated microscopic poliangiitis providing a potential correlative picture in human pathology. These data provide the first demonstration that NET structures are highly immunogenic such to trigger adaptive immune response relevant for autoimmunity.